Evaluation of Relationship Between 2 Hours Post-Prandial Glucose Level and Hba1c Levels in Diabetic Patients: A Cross-Sectional Study (Journal of Medical & Health Sciences Review, 2026)
Postprandial hyperglycemia is an important contributor to overall glycemic burden and cardiovascular risk in type 2 diabetes mellitus. While glycated hemoglobin (HbA1c) reflects long-term glycemic control, 2-hour postprandial plasma glucose (2h-PPG) captures acute meal-induced glucose excursions. Clarifying the relationship between these measures can enhance diabetes management and therapeutic targeting. The Objective of this study was to investigate the correlation between 2h-PPG and HbA1c levels in diabetic patients compared with apparently healthy controls. This cross-sectional analytical study included 400 participants; 200 patients with type 2 diabetes and 200 age- and sex-matched controls. Fasting blood samples were collected to determine baseline glucose and HbA1c, followed by a 2h-PPG assessment after a standardized meal. HbA1c was measured using high-performance liquid chromatography, and plasma glucose levels were determined by the glucose oxidase-peroxidase method. Pearson correlation coefficient quantified the relationship between 2h-PPG and HbA1c. Among diabetic patients, 184 (92%) exhibited 2h-PPG >200 mg/dL and HbA1c >6.5%. Pearson correlation analysis demonstrated a strong positive correlation between 2h-PPG and HbA1c (r = 0.82, p < 0.001), indicating that higher postprandial glucose levels were closely associated with elevated long-term glycemic indices. No significant correlation was observed in controls (r = 0.12, p = 0.10). These findings underscore the importance of monitoring postprandial glucose in addition to HbA1c for comprehensive diabetes management. Targeting postprandial hyperglycemia may improve overall glycemic control, reduce cardiovascular risk, and optimize therapeutic outcomes in type 2 diabetic patients.